2010
DOI: 10.1002/asl.277
|View full text |Cite
|
Sign up to set email alerts
|

A robust method to determine global distribution of atmospheric boundary layer top from COSMIC GPS RO measurements

Abstract: In this study, we introduce a robust method for precise determination of atmospheric boundary layer (ABL) top from COSMIC global positioning system radio occultation measurements. We apply a wavelet covariance transform to compute the convolution of COSMIC-observed bending angle/refractivity profile with a Haar function and use the maximum covariance to identify the ABL top, making detection of even small transitions possible. Results obtained were compared with radiosonde N profiles for verification of the AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…RO observations may be used to develop ABL climatologies, such as the spatial and temporal variations of the ABL (von Engeln et al, 2005;Sokolovskiy et al, 2007Sokolovskiy et al, , 2010Ao et al, 2008;Ratnam and Basha, 2010). The CHAMP climatology agreed well with the ECMWF analyses over this period, especially over the oceans.…”
Section: Profiling the Atmospheric Boundary Layermentioning
confidence: 55%
“…RO observations may be used to develop ABL climatologies, such as the spatial and temporal variations of the ABL (von Engeln et al, 2005;Sokolovskiy et al, 2007Sokolovskiy et al, , 2010Ao et al, 2008;Ratnam and Basha, 2010). The CHAMP climatology agreed well with the ECMWF analyses over this period, especially over the oceans.…”
Section: Profiling the Atmospheric Boundary Layermentioning
confidence: 55%
“…All these studies showed that COSMIC specific humidity compares well with radiosonde, reanalysis, and other satellite data sets. In troposphere, the contribution of water vapor is more in refractivity than temperature Ratnam & Basha, 2010). However, the refractivity data from GPSRO satellite is very accurate from the surface to 40 km.…”
Section: Methodology To Identify the Itczmentioning
confidence: 99%
“…In addition, it includes both temperature and water vapor information. Using limited data, Ratnam and Basha (2010) also demonstrated the use of GPSRO refractivity to locate the ITCZ. Note that changes, which occur in lower troposphere, can significantly appear in refractivity, whereas in upper troposphere temperature controls the refractivity due to less amount of water vapor contribution.…”
Section: Methodology To Identify the Itczmentioning
confidence: 99%
“…A few studies have been done by using Global Positioning System radio occultation (GPS RO) measurements (Ratnam and Basha, 2010;Guo et al, 2011;Ao et al, 2012) or Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) (McGrath-Spangler and Denning, 2013). GPS RO provides a valuable global view of the height-resolved refractivity or moisture structure of ABL.…”
Section: Introductionmentioning
confidence: 99%